Comment on the Chilean constitutional reform project - Zúñiga Urbina, Francisco (2019)
This paper analyses and makes a critical balance of the Chilean constitutional reform project, sent by the President of the Republic to the Senate. The objective of the constitutional reform project is to elaborate a democratic New Constitution, in contrast to the current constitution that is a product of an institutional rupture. To do that there was a participatory process of citizenship that culminates with the “Citizens Bases for a New Constitution”, also, an Indigenoues Constituent Process was made.